Board Gender Diversity and the Indian Banking Sector: A Bibliometric Analysis. Issue 2 (December 2022) - Bhatia, Monika; Bhullar, Pritpal Singh; Roy, Dipayan; Tandon, Deepak
This paper aims at identifying the probable impact of board gender diversity on the key business operational areas explored by the existing published research. Moreover, the study also emphasises exploring the role of board gender diversity in the Indian banking sector. The data from existing literature from 2000 to 2022 have been extracted from the Scopus database. By devising VOSviewer software, citation analysis and bibliographic coupling analysis were conducted to identify the influential documents, authors and journals that made significant contributions to this segment of research. According to the findings of the study, no significant research has been conducted to determine the impact of board gender diversity on various key operational aspects of the banking sector. It also discovers that the majority of the studies were carried out in European countries. The Indian context is still underexplored. The study suggests key research questions, the answers to which can be investigated by future researchers.